Ultrastructural charachteristic of benign and anaplastic meningiomas - S. I. Tertishniy; V. A. Shavrin; W. E. Voteva; K. L. Dikiy (Zaporozhye State Medical University, 2017)
Taking into account high prevalence of meningiomas (35 %) among other intracranial tumors and variety of their histological structure, electron microscopy (EM) can provide important diagnostic information and be substantially complementary to light microscopy data and immunohistochemical studies. Objective: to study ultrastructural changes in benign and anaplastic meningiomas and to establish the main differential diagnostic ultrastructural features of meningiomas of different grades. Material and Methods: light microscopy and EM studies were conducted using 35 cases of meningioma. Results: Our EM data allow highlighting the characteristic ultrastructural changes in different subtypes of benign meningiomas. In particular, meningothelial subtype comprised of cells with homogeneous structure with light oval nuclei, with evenly arranged finely granular chromatin, well differentiated cell-cell contacts such as desmosomes. Cytoplasmic membranes of adjacent cells adhered to one another, forming small intussusceptions sometimes, which penetrated into the neighboring cells, which significantly increased the contact area of adjacent cells. Fibroblastic meningiomas were rich in modified fibroblasts, which contained bizarre nuclei of irregular shape with compact chromatin arrangement near the nuclear membrane. Also there were plenty bundles of collagen fibrils with the orderly assembled collagen fibers as well as with a chaotic arrangement. Transitional meningiomas were characterized by the combination of meningothelial like areas and areas of typical fibroblastic differentiation. EM changes were similar to meningothelial and fibrous meningiomas. Anaplastic meningiomas were characterized by increased in size or pyknotic nuclei, presence of nuclei with deep intussusceptions, a significant dilution of chromatin structure, focal disturbances of karyolemma integrity, vacuolization of intracellular membrane structures and extracellular edema, a significant reduction of cell-cell contacts. Conclusions: The ultrastructural features of benign meningiomas are reflected in the presence of desmosomes in meningothelial subtypes, a significant number of collagen fibrils in the fibroblastic subtypes, which confirms the double epithelial-mesenchymal histogenesis of these tumors. The cells of anaplastic meningiomas were characterized by marked signs of nuclear polymorphism, processes of alteration such as karyopyknosis and apoptosis, as well as a significant reduction of cell-cell contacts, which can promote recurrence and possible metastasizing.